Gas-assisted electrospinning of high-performance ceramic fibers: Optimal design modelling and experimental results of the gas channel of the nozzle - Guojie Xu; Guojie Xu; Guojie Xu; Mingyi Chen; Mingyi Chen; Mingyi Chen; Yufei Gao; Ying Chen; Ying Chen; Zhifeng Luo; Zhifeng Luo; Han Wang; et al. (Frontiers in Materials, 2023)
Electrospinning (ES) of ceramic fibers has mostly remained in the research level, which can be because of the hard process and parameters controlling the low rate of production. The yield of fiber production by solution blow spinning (SBS) is exciting but the production process is unstable due to the reverse flow phenomenon. In this paper, we prepared high-performance ceramic fibers by gas-assisted electrospinning (GES), which combined the advantages of ES and SBS. Also, comprehensive numerical and experimental analysis for nanofibers produced using GES are provided. The gas flow characteristics through different parameters' nozzle were investigated numerically using computational fluid dynamics and experimentally in a custom-built gas-assisted electrospinning setup to produce SiO2 nanofibers.